Pengembangan Kewirausahaan dan Daya Saing Usaha Kecil Menengah Menuju Era Kemandirian dan Digitalisasi pada UKM Mpok Eneng di Wilayah Pulo Gebang Jakarta Timur - Achmad Jaelani; Arsid; Winaya Purwanti (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Pletok beer is one of the legendary culinary drinks in Jakarta, where its existence is difficult to find but is still in demand for consumption by the public, especially in the DKI Jakarta area. Pletok beer is a typical Betawi drink tempoe doloe made from native Indonesian spices that are useful and nutritious for health. There is no doubt about the benefits of this drink for the health of the body, because the raw materials consist of ginger, sappan wood, cinnamon, lemongrass leaves and other native Indonesian spices. Pletok beer is drunk in warm conditions, it is very delicious to drink cold it will also be more delicious, it can also be drunk as a mixture with herbal drinks to get rid of colds when going to bed at night. The purpose of this community service activity is to improve management, marketing and financial governance in the Mpok Eneng pletok beer business in the Pulo Gebang area, East Jakarta, so that pletok beer products can be known in the Greater Jakarta area and nationally. The implementation of this community service activity was carried out for 6 months originating from the DIPA of the Directorate of Research, Technology and Community Service, the Directorate General of Higher Education, Research, and Technology of the Ministry of Education, Culture, Research, and Technology for the 2022 Fiscal Year. These activities include conduct training and mentoring for partner management and business governance, finance, training and production management, packaging and marketing, as well as training and assistance for information systems/digitalization. The results of this community service activity are partners can manage their products with attractive packaging, increase product marketing through online and manage finances and good management.